(untitled) (Research, Society and Development, 2021)
Choroidal melanoma is the most common cancer to affect the eye in adults - it is also called ocular melanoma or uveal melanoma. The annual incidence of ocular melanoma is approximately 10 cases for every million inhabitants, which means that for every million people we have 10 cases a year. In Brazil we have approximately 2,000 cases of this disease per year. To meet the objectives of the work, an integrative quantitative and qualitative literature review was carried out, in which the following steps were followed: definition of the theme and elaboration of the research question; elaboration of the eligibility, inclusion and exclusion criteria of the studies; definition of descriptors, literature search and data collection; critical analysis of included studies and discussion of results; and presentation of the review summary. Due to the high mortality that the disease presents, associated with the great importance that the visual function and visual aesthetics have in the integration of the individual with the social environment, the importance of early diagnosis and treatment of the disease is highlighted.